Faktor Pendorong Kepulauan Solomon Menyepakati Kerja Sama Belt and Road Initiative (BRI) dengan Tiongkok pada tahun 2013-2019 (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
Solomon Islands decided to shift their diplomatic recognition to China after having diplomatic relations with Taiwan over 36 years. China and Taiwan are two countries that have rivalries in the South Pacific in their capability to provide diplomatic recognition. The influence of China in the South Pacific increase due to Belt and Road Initiative (BRI) program that provide assistance of infrastructure development. China economic increased influence has an impact on changes in regional geopolitical maps, also influencing the foreign policy of the region countries including Solomon Islands. This research is to explain the determinants of Solomon islands foreign policy to shift diplomatic recognition and sign BRI. The writer of this research use theory determinants of foreign policy by William D. Coplin